Sistem Informasi Bimbingan Tugas Akhir Berbasis Web Pada Universitas Adiwangsa Jambi - Rahmadani, Novella; Effiyaldi , Effiyaldi (Jurnal Manajemen Sistem Informasi, 2022)
Adiwangsa University Jambi is one of the private educational institutions, wherein running its business is pursuing the role of information technology, such as final project guidance activities which are currently still carried out conventionally, namely face-to-face. This often causes problems, especially during the pandemic which has quite an impact on graduation or guidance. To overcome the existing problems, the author proposes the design of a web-based final project guidance information system in the form of a prototype that can be implemented in the future so that it can be a solution. The tools used in modeling this system are use case diagrams, activity diagrams, and class diagrams. The results of this study are in the form of a web-based final project guidance information system prototype that can help smooth the course of final project guidance activities at Adiwangsa University Jambi.